3(2x+2)=6(1+8x)

Simple and best practice solution for 3(2x+2)=6(1+8x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2x+2)=6(1+8x) equation:


Simplifying
3(2x + 2) = 6(1 + 8x)

Reorder the terms:
3(2 + 2x) = 6(1 + 8x)
(2 * 3 + 2x * 3) = 6(1 + 8x)
(6 + 6x) = 6(1 + 8x)
6 + 6x = (1 * 6 + 8x * 6)
6 + 6x = (6 + 48x)

Add '-6' to each side of the equation.
6 + -6 + 6x = 6 + -6 + 48x

Combine like terms: 6 + -6 = 0
0 + 6x = 6 + -6 + 48x
6x = 6 + -6 + 48x

Combine like terms: 6 + -6 = 0
6x = 0 + 48x
6x = 48x

Solving
6x = 48x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-48x' to each side of the equation.
6x + -48x = 48x + -48x

Combine like terms: 6x + -48x = -42x
-42x = 48x + -48x

Combine like terms: 48x + -48x = 0
-42x = 0

Divide each side by '-42'.
x = 0

Simplifying
x = 0

See similar equations:

| (y+1)=2(x-3) | | 9c-15=4c | | 8(4x+1)=9(5x-2) | | 10x^9-17x^7+7x^6= | | 5x-1/2x=18 | | 5(x-90)-4(x+150)=950 | | x+x/2+4=30 | | 8(d+5)=23 | | 4x^2+8-12=0 | | n^2+8=-6n | | 3(7+c)=60 | | 52000-8n=18000+8n | | 8(4x+1)=14(2x-3) | | [3(m-5)+16]-[2(3m-3)+5]= | | -3+5(2x-17)=1 | | a(x-a)=1 | | 3(7+c)=51 | | w/4.3-9.8=70 | | 7-6u=5u+19 | | 4n-3n+2=5 | | 4-9x=4x+27 | | -17+6x-2x=11 | | 4(3x+8)-4=7(2x-1)+3x | | 12a^6b^6+6ab^4-30ab^6= | | 2r-9=13 | | 5x-1=3(x)+9 | | (2-3a)/4=5 | | (4/x)=(1/4)x | | P+3Y=164 | | (2-3a)/45 | | -1+8(1+4x)=199 | | 5x+125-x=100 |

Equations solver categories